Social Politics of Civil Society - Chyzhevska, Maryna; Chyzhevskyi, Vladyslav (Historia i Polityka, 2017)
This paper presents a cross-cultural overview of the features of the dynamics of the perception of the concepts of “society”, “politics”, and “state”. The work raises the issue of complex and multifaceted individual consciousness of understanding policy. Authors formulate this aspect from the perspective of historical dynamics and propose to explore the process of transformation of the ancient city-state and flowing therefrom political relations in the modern state with its complex political system. It was stressed that the problem of understanding the nature and role of social policy is complicated by language as well as etymological and conceptual differences.